Template-controlled piezoactivity of ZnO thin films grown via a bioinspired approach - Blumenstein, Nina J.; Streb, Fabian; Walheim, Stefan; Schimmel, Thomas; Burghard, Zaklina; Bill, Joachim (Beilstein Journal of Nanotechnology, 2017)
Biomaterials are used as model systems for the deposition of functional inorganic materials under mild reaction conditions where organic templates direct the deposition process. In this study, this principle was adapted for the formation of piezoelectric ZnO thin films. The influence of two different organic templates (namely, a carboxylate-terminated self-assembled monolayer and a sulfonate-terminated polyelectrolyte multilayer) on the deposition and therefore on the piezoelectric performance was investigated. While the low negative charge of the COOH-SAM is not able to support oriented attachment of the particles, the strongly negatively charged sulfonated polyelectrolyte leads to texturing of the ZnO film. This texture enables a piezoelectric performance of the material which was measured by piezoresponse force microscopy. This study shows that it is possible to tune the piezoelectric properties of ZnO by applying templates with different functionalities.
Keywords: piezoresponse force microscopy; template-controlled deposition; ZnO